Maternal and perinatal effects with the use of floral therapy in childbirth: randomized clinical trial - Anna Paula Frassom da Silva Magaton; Sônia Regina Godinho de Lara; Maria Cristina Gabrielloni; Márcia Barbieri (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To evaluate the clinical, obstetric, maternal and perinatal effects of the use of flower essences in labor, against factors that enhance it. Method Clinical trial, randomized, controlled, in 164 parturients divided into two groups, flower essences and placebo, respectively, evaluated before and after the intervention. Carried out in a vaginal delivery center, in the city of São Paulo, from May to October 2018. Data were analyzed using descriptive statistics, Student's t test, bilateral hypothesis, negative and positive observed critical t, Pearson's chi-square, exact test. Fisher. Results It was observed in the Experimental Group, moderate increase in systolic blood pressure (p=0.046), frequency (p=0.055) and intensity of contractions (p=0.031), as well as a reduction in time to birth (194 minutes), higher number of vaginal deliveries (p=0.038) and better pattern of fetal vitality. Conclusion There was evidence of a positive action of the Floral Essence on the potentiating factors of labor, being effective in maternal clinical and obstetrical repercussions, as well as perinatal ones.